EFFECT OF TRADE OPENNESS ON THE ENVIRONMENTAL PERFORMANCE INDEX IN SUB-SAHARA AFRICA - Wicaksana, Tania; Karsinah, Karsinah (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
A possible solution to overcome the dilemma between trade openness and the environment can be done by adjusting the factors that might affect the environmental performance index. However, this can only be done if there is an established relationship between the influencing factors. The purpose of this study was to analyze the effect of trade openness, energy, technology, and population on the environmental performance index in Sub-Saharan Africa. This type of research is a quantitative research using panel data regression analysis tool. Trade openness, energy, and population have a positive and significant influence on the environmental performance index in Sub-Saharan Africa.